Marginal bone loss of two implant systems with three different superstructure materials: a randomised clinical trial. (16th April 2013) - Türk, A. G.; Ulusoy, M.; Toksavul, S.; Güneri, P.; Koca, H.
Summary Marginal bone level is a criterion for implant success. The aetiological factors of bone loss have not been clarified. The aim of this study was to evaluate the influence of implant systems and prosthetic materials on the marginal bone loss. Twenty‐three patients participated; two implant systems and three superstructure materials were used in this study. Twenty‐two of the implants were restored with porcelain fused to base metal alloy (BMA), 25 with porcelain fused to noble metal alloy (NMA) and 20 with zirconium oxide‐based ceramics. Radiographs were taken at baseline and 3, 6 and 12 months after loading. Crestal bone‐level changes were assessed with digital subtraction radiographs. The effects of superstructure materials and implants were evaluated with one‐way anova and independent samples t‐test, respectively (α = 0·05). The mean crestal bone loss was found 0·483 mm in 3 months, 0·622 mm in 6 months and 0·816 mm in 12 months. Prosthetic materials were found to have greater effect (β = 0·575, P = 0·015) on crestal bone loss than implant systems (P > 0·05). The porcelain fused to BMA restorations showed higher crestal bone loss than NMA‐based restorations (P = 0·003) at 3 months, (P = 0·038), at 6 months and (P = 0·00) at 12 months; however, crestal bone loss differences between NMA and zirconia were not significant (P = 0·629) at 3 months, (P = 0·974) at 6 months and (P = 1) at 12 months. Within the limitations of this study, our results revealed that rather than the implant systems, prosthetic materials seemed to have an effective role on crestal bone.